Parameter Genetik Beberapa Karakter Kuantitatif Galur S3 Tanaman Jagung di Lahan Kering - Sudika, I Wayan; Sutresna, I Wayan; Anugrahwati, Dwi Ratna (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
This research aims to determine genetic diversity, broad heritability and genotypic correlation of several quantitative characters of the S3 line of corn plants in dry land. Treatment of 30 S3 lines, arranged in a randomized block design, two replications. The characters observed included the variables of flowering, growth, yield components, yield and maturity. The observation data were analyzed using analysis of variance at 5 percent significant level, then genetic variance, phenotypic variance, heritability and genetic diversity coefficient were calculated. Genotypic correlation analysis was also carried out in this study. The results show that ASI and yield have wide genetic diversity; while cobs dry weight per plant is classified as medium and other characteristics are classified as narrow. Heritability in a broad sense is relatively high, obtained at silking time, harvesting time and yield. Eight other characters have moderate heritability and the rest have narrow heritability. A high negative genotypic correlation with leaf angle was obtained for leaf area; while the other four characters have a low negative correlation. Harvesting time had a low positive correlation with flowering variables; other characters are not correlated. Yield was highly positively correlated with plant height; while cob length, cob diameter and cob weight were moderately positively correlated. Plants selected for selfing in the next generation are taller plants, with more leaves and earlier silking time.